2022
DOI: 10.4103/jmu.jmu_218_21
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography for Assessment of Testicular Stiffness in Patients with Varicocele

Abstract: Background: The purpose of this study was to use ultrasonography and shear wave elastography (SWE) to assess stiffness and volume of testes in adult patients with varicocele, to compare the results with those of normal contralateral testes of the same patients and healthy testes of control subjects. Methods: In this IRB-approved prospective comparative study, 58 patients with varicocele (116 testes) and 58 control patients (116 testes) were enrolled. A total of 66 teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to current literature, it is clear that age and BMI [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , varicocele grade [28] , [29] , [30] , [31] and testicular elasticity modulus [32] , [33] , [34] , [35] have a definite impact on male fertility and sperm quality. Interestingly, the multivariate logistic regression analysis showed that BMI had no predictive value for the improvement of sperm parameters after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to current literature, it is clear that age and BMI [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , varicocele grade [28] , [29] , [30] , [31] and testicular elasticity modulus [32] , [33] , [34] , [35] have a definite impact on male fertility and sperm quality. Interestingly, the multivariate logistic regression analysis showed that BMI had no predictive value for the improvement of sperm parameters after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Elastographic examinations were conducted with minimal compression for at least 5 seconds to reduce motion artifacts. ROIs (regions of interest) were placed to measure a round area of 0.1 cm2 in the central part of the normal testicular parenchyma, as it is known that measurements become more standardized in this region, and the area becomes smaller in SWE [4,5].…”
Section: Usg Swe Device Technique Assessment Data Collection and Outc...mentioning
confidence: 99%
“…In human medicine, testicular stiffness has been investigated by elastography in both physiological (10) and pathological testes (11)(12)(13)(14)(15)(16)(17)(18). Elastography has been applied for the evaluation of undescended testes, infertility, testicular torsion, tumors, microlithiasis, varicocele and segmental testicular infarction (18), and has shown efficacy in the diagnosis of varicocele (19) and in discriminating focal non-neoplastic lesions from neoplasms, and benign from malignant testicular tumors (20).…”
Section: Introductionmentioning
confidence: 99%